Pengawasan Lalu Lintas Udara di Wilayah Perbatasan Negara - Triadi, Irwan; Rahman, Naila Kamila; Amanda, Nur Septiana; Elvira, Olga; Oktaviani, Eka Putri; Julius, Tambok; Faidzuddin, Achmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
: Air traffic control in border areas is a crucial aspect in maintaining national sovereignty and security. This study aims to assist in the regulation of laws and challenges faced in managing air traffic in border areas. The research method uses a juridical-normative approach by reviewing various national and international laws and regulations related to aviation and airspace sovereignty. The results of the study show that each country has full control over its airspace based on the 1944 Chicago Convention and UNCLOS 1982. Indonesia itself has regulated air traffic control through Law No. 1 of 2009 concerning Aviation, which affirms the state's right to regulate and supervise airspace for national interests. The main challenges in supervision include coordination between countries, security, geographical constraints, differences in regulations, and growth in air traffic volume. The study provides a collaborative approach through strengthening international cooperation, investing in advanced technologies such as AI and satellite systems, and involving all stakeholders. This study emphasizes the importance of a strong and integrated oversight mechanism to protect the airspace ecosystem from external threats and violations of the law.